2004
DOI: 10.1002/pen.20249
|View full text |Cite
|
Sign up to set email alerts
|

Design of calibrators for extruded profiles. Part I: Modeling the thermal interchanges

Abstract: The parameters influencing the calibration/cooling stage of profile extrusion are discussed, and a numerical finite-volume method code to model the heat transfer is described and validated. For this purpose, the numerical predictions are compared with the analytical solution of a simple problem, with results available in the literature and with those produced by a commercial software. The routines developed are then used to identify the main process parameters and boundary conditions and to estimate their rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…However, the development of a general approach for the problem requires the employment of 3D models, which can cope with all the phenomena involved. 6 In terms of optimisation of the calibration/cooling stage, some work has been carried out concerning the layout/ diameter of the cooling channels, using 2D models. 7 A prior study 6 performed with an in house developed 3D numerical code based on the finite volume method, showed that, in general, when a reduction of the extruded profile average temperature is imparted, lower temperature homogeneity is also obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the development of a general approach for the problem requires the employment of 3D models, which can cope with all the phenomena involved. 6 In terms of optimisation of the calibration/cooling stage, some work has been carried out concerning the layout/ diameter of the cooling channels, using 2D models. 7 A prior study 6 performed with an in house developed 3D numerical code based on the finite volume method, showed that, in general, when a reduction of the extruded profile average temperature is imparted, lower temperature homogeneity is also obtained.…”
Section: Introductionmentioning
confidence: 99%
“…6 In terms of optimisation of the calibration/cooling stage, some work has been carried out concerning the layout/ diameter of the cooling channels, using 2D models. 7 A prior study 6 performed with an in house developed 3D numerical code based on the finite volume method, showed that, in general, when a reduction of the extruded profile average temperature is imparted, lower temperature homogeneity is also obtained. The exceptions were the reduction of the extrusion velocity and splitting the calibrator into several units separated by annealing zones, in which the temperature of the extrudate tends to equalise, allowing for the relaxation of the thermal induced stresses and increasing the heat transfer efficiency of the subsequent calibrator.…”
Section: Introductionmentioning
confidence: 99%
“…Reifschneider et al [12] used numerical modelling to design an extrusion die for the production of a U shaped profile, and to evaluate the heat transfer at its calibration stage. More recently, the thermal design of calibrators was the subject of several works authored by Nóbrega et al [13][14][15][16]. For this purpose they developed a numerical code, based on the finite volume method (FVM), able to model the 3D heat transfer phenomena that take place during the cooling stage.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent contributions for the cooling stage modelling are the works of Mousseau et al [17] and Carneiro et al [18], who produced experimental devices able to quantify the heat transfer coefficient (or contact resistance) at the profilecalibrator interface. This heat transfer coefficient has a significant role on the profile extrusion cooling stage performance [13], being its detailed characterization essential to accurately model the system temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] What is more, the technology of finite element (FE) simulation is widely used in the design on the mould, which greatly cuts down the cycle of design and shows huge advantage. [7][8][9] For the precision of a forged titanium-alloy turbine blade, Morita et al 10 used FE simulation to define the optimum position of the billet. Lapovok 11 optimized the design of the preform with reference to die-life and damage accumulation.…”
Section: Introductionmentioning
confidence: 99%